Mn-Ln complexes based on azo-salicylaldehyde: Synthesis, structure and magnetic properties. (1st January 2023) - Yang, Meng; Huang, Shuyuan; Zhang, Tian; Yu, Xiaoxuan; Kuang, Xiaoman; Dong, Wen
Graphical abstract: Abstract: Three Mn-Ln complexes of [MnLn2 (TTMSA)4 (HTTMSA)2 (H2 O)6 ] [Mn(H2 O)6 ]·4H2 O (H2 TTMSA = 5-azotetrazolyl-3-methoxysalicylaldehyde, Ln = Gd (1 ), Ho (2 ), Er (3 )) have been synthesized and structurally characterized. The structural characterization reveals that the Mn 2+ ion adjusts two mononuclear [LnL3 (H2 O)2 ]2 parts into tri-nuclear [LnL3 (H2 O)2 ]2 Mn 2− cluster and additional [Mn(H2 O)6 ] 2+ just as counter ion to keep electric neutrality of the molecule. The ac susceptibility measurement revels that both complexes of 2 and 3 show slow magnetic relaxation process.